On the Early Diagnosis of Basal Cell Carcinoma (Case Description) - M. A. Gomberg; Z. R. Khismatullina; N. K. Fayzulin; A. M. Titoyan (Креативная хирургия и онкология, 2020)
Introduction. Basal cell carcinoma represents one of the most common malignant skin tumours. This malignant skin neoplasm is characterised by slow growth and a weak tendency to metastasis, although the fatal outcome with an aggressive tumour growth is also possible. On the example of a clinical case, an analysis of diagnostic errors regarding this disease was carried out.Case Description. Patient B., 67 years old, sought medical assistance in the Republican Dermatovenerologic Dispensary with complaints of a lesion on the nasal dorsum. The anamnesis indicated that the patient initially turned to a dermatologist at the place of residence, who prescribed a combined dermatic treatment containing a topical corticosteroid. Due to the lack of dynamics, the patient suggested a neoplasm and sought medical assistance from an oncologist at his place of residence. After excluding oncological pathology, the oncologist recommended observation and treatment by a dermatologist.Results and discussion. Repeatedly, the patient requested medical assistance only after a year and a half with complaints of an increase in the lesion on the nasal dorsum, the appearance of black crusts and bleeding. The results of a dermatoscopic examination demonstrated the absence of a pigment network, thus confirming the tumour process of non-melanocytic skin lesion. Based on the data of the clinical examination and histological examination of the tumour biopsy, the assumption was confirmed and the diagnosis of st. I T1N0M0 gr. III nasal skin cancer, was made. Under the conditions of the Republican Dermatovenerologic Dispensary, the patient underwent X-ray therapy according to the radical program in 5 days a week by the Xstrahl-300 (0545) instrument with the single and summary tumour doses on the area of the nasal skin tumour equal to 400 and 4000 cGy, respectively. Positive dynamics was noted (the lesion focus was epithelised) and the patient is currently under the supervision of an oncologist at the place of residence.Conclusions. The lack of proper examination by a dermatologist and oncologist at the place of residence contributed to the progression and growth of a malignant neoplasm in the patient. The diagnostic significance of the dermatoscopic method in the early stages of the malignant tumour process is substantiated.